Faktor Dasar Dan Ajar Dalam Hubungannya Dengan Peran Ibu Terhadap Pendidikan Anak - Didik Supriyanto (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2015)
This research focused on the problem whether the Holy Qur'an contains a concept the basic and the instructive relating to the process of children’s education. As one of the Holy Books revaluated to the Prophet Muhammad (peace be upon him), the Holy Qur'an is the unquestionable truth to guide the human beings in the world and the hereafter. To explore the assumption on the two concepts in the Holy Qur'an, it is applied three models of approach: descriptive, comparative and analysis approach. And the will cover the related Qur'anic verses with the main discussion, also present some interpretations of the Qur'anic passages taken from the references of mufaseers and the Prophet’s traditions (al-hadith). It also performs some related theories from the legible Muslim analysts. All these process will arrive at the scientific inference. Every man naturally disposed the basic factor should be developed because he is the agent of the world. The basic will be disappeared if it is not continually stimulated or if it puts aside the instructive factor. A conclusion of the problem is that the development of the children in the Holy Qur'an runs to the law of disposition. It means that the man naturally has the basic and the innate. The basic will become real on the surface if it is encouraged by he inner or outer senses. The implementation of education believes that the man (the children) owns the basic potentially and it is developed through teaching or education process.